Synthesis, Characterization and Evaluation of Starch Acetate as Rate Controlling Matrix Former for Controlled Release of Glipizide - Chowdary, K.P.R.; Radha, G.V. (Asian Journal of Chemistry, 2010)
Starch acetate with a degree of substitution of 1.48-1.50 could be synthesized by acetylation ofpotato starch with acetic anhydride. Matrix tablets of glipizide (10 mg) prepared employing starch acetate as matrix former in different proportions gave slow and controlled release over more than 24 h. Glipizide release was diffusion controlled and dependent on strength (%) of starch acetate and type of diluent in the tablets. Non-fickian diffusion was the release mechanism from these tablets. A good linear relationship was observed between per cent of polymer, starch acetate and release rate (K0) of the matrix tablets. Release rate of the matrix tablets was stable and unaltered during short time accelerated stability study. Starch acetate was found suitable as matrix former for controlled release and the matrix tablets of glipizide formulated employing starch acetate (5 %) gave controlled release of glipizide over 24 h.